¡ Esos no son faite! – Esprit rebelle en crise et transformations d’une scène artistique à Lima - Lucie Miramont (Caravelle)
The crisis in Peru can be considered as a structural element, a real backdrop for political, economic, social and environmental stages. Through the day-to-day speeches and practices of an independent artistic stage in Lima, we aim at understanding the resorts employed by artists  in order to develop their activity while maintaining their image of protesters and anti- establishment crowd. Between underground economy, self-management, identity-driven positioning and mass rejection of the political class, the dynamic that rules this stage appears in their verses and often between the lines.